Comparative risk of oral ulcerations among antipsychotics users – population‐based retrospective cohort study. Issue 2 (9th November 2015) - Lai, Edward Chia‐Cheng; Hsieh, Cheng‐Yang; Wong, Monera B.; Lin, Swu‐Jane; Yang, Yang‐Kuang; Kao Yang, Yea‐Huei; Setoguchi, Soko
Abstract: Purpose: The study aimed to evaluate the comparative risk of oral ulcerations among antipsychotic medications. Methods: We analyzed the National Health Insurance Research Database of Taiwan and included patients newly initiated with a single antipsychotic agent including haloperidol, sulpiride, olanzapine, quetiapine, risperidone, or amisulpride during 2002 to 2010. The outcome of interest was oral ulceration, defined by the presence diagnoses of stomatitis and mucositis, aphthous‐like ulceration and oral burns, or dispensing of stomatological corticosteroids included triamcinolone, dexamethasone, hydrocortisone, and prednisolone. We conducted Cox proportional hazards regression to compare the risks of oral ulceration among antipsychotics. Results: The rate of oral ulcerations was highest in the amisulpride group (217.7 per 1000 person‐year), followed by quetiapine (193.9 per 1000 person‐year), olanzapine (161.9 per 1000 person‐year), sulpiride (147.1 per 1000 person‐year), risperidone (115.6 per 1000 person‐year), haloperidol (107.5 per 1000 person‐year) and aripiprazole (49.8 per 1000 person‐year). Compared with haloperidol users, the adjusted hazard ratio (AHR) was 1.40 (95% CI, 1.12–1.73) in olanzapine, 1.48 (95% CI, 1.30–1.69) in quetiapine, 1.27 (95% CI, 1.19–1.44) in sulpiride, 1.68 (95% CI, 0.97–2.59) in amisulpride, 1.02 (95% CI, 0.83–1.45) in risperidone, and 0.41 (95% CI, 0.24–0.72) in aripiprazole users by Cox regression model. Conclusion: Olanzapine, quetiapine, and sulpiride posed a higher risk, while aripiprazole posed a lower risk of oral ulcerations compared with haloperidol in subjects with newly initiated antipsychotic therapy. Risperidone and amisulpride tended to have higher risk of oral ulcerations, but this was not statistically significant. Copyright © 2015 John Wiley & Sons, Ltd.